2010
DOI: 10.1098/rspb.2010.0452
|View full text |Cite
|
Sign up to set email alerts
|

Population size predicts technological complexity in Oceania

Abstract: Much human adaptation depends on the gradual accumulation of culturally transmitted knowledge and technology. Recent models of this process predict that large, well-connected populations will have more diverse and complex tool kits than small, isolated populations. While several examples of the loss of technology in small populations are consistent with this prediction, it found no support in two systematic quantitative tests. Both studies were based on data from continental populations in which contact rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
255
2
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(271 citation statements)
references
References 15 publications
13
255
2
1
Order By: Relevance
“…In such situations, other factors may be equally, if not more, important. The results of a recent study by Kline & Boyd [32] are consistent with this idea. Kline & Boyd used data from Polynesian fisher -farmer populations to test the hypothesis that population size influences cultural evolution.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In such situations, other factors may be equally, if not more, important. The results of a recent study by Kline & Boyd [32] are consistent with this idea. Kline & Boyd used data from Polynesian fisher -farmer populations to test the hypothesis that population size influences cultural evolution.…”
Section: Discussionsupporting
confidence: 82%
“…If risk of resource failure was not the main influence, what was? Based on the findings of Henrich [14] and Kline & Boyd [32], population size is an obvious possibility to investigate. The study reported by Rendell et al [34] suggests that degree of reliance on copying may also be worth considering.…”
Section: Discussionmentioning
confidence: 99%
“…These topics are non-exclusive and non-exhaustive, and they are intended to provide an initially broad set of targets for identifying external influences on tool use. In recent years, researchers have explored the relevance of the number of interacting individuals to the maintenance of traditions, showing that an increase in social contacts can allow for new ideas and techniques to be retained and spread more readily in a population [39][40][41][42]. The principle is not restricted to the human lineage [43], and wild orangutans and chimpanzees have been found to display increased complexity, success and frequency in tool use in increasingly social and higher population density settings [44][45][46].…”
Section: (B) Factors Promoting Captivity Biasmentioning
confidence: 99%
“…-Innovations and population growth are expected to be mutually reinforcing. Features of a population including its size, social interactions and established standards [102,105,106] influence the probability of innovation. Innovation may foster ecological opportunity, which in turn promotes population expansion and adaptive radiation [14,107].…”
Section: (A) Searching For and Discovering Innovationmentioning
confidence: 99%